The Influence Of Demography And Risk Tolerance Toward Portfolio Invesment Selection Of Post Graduate Students - Farah Margaretha Leon, Cindy Hadinata (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
The purpose of this research is to give empiric evidence from the influence of demography variable toward portfolio investment selection and risk tolerance also the influence of risk tolerance toward portfolio investment selection.Â Â The methodology of this research was used primer data by questionnaire both online and offline to postgraduate students in Jakarta. Data succeeded to be collected for 258 respondents and data analyze method used descriptive statistic, coefficient concordance Kendall W and chi square analyze. The result of this research showed that demography variable significantly influence to investor risk tolerance for Postgraduate students in Jakarta. Gender and age significantly influence to risk tolerance and occupation is not influence to investor risk tolerance for Postgraduate students in West Jakarta. Meanwhile for gender significantly influence to investment portfolio selection. Risk tolerance significantly influence to investment portfolio selection for postgraduate students in West Jakarta. Â The implication for investor and investment advisor should understand the demography variable and investor risk tolerance level, therefore they make right investment.